DISKRIMINASI GENDER DALAM NOVEL PEREMPUAN TERPASUNG KARYA HANI NAQSHABANDI: KAJIAN FEMINISME SASTRA - Reski Rahmayati; Syahrul Ramadhan; Afnita Afnita (Kajian Linguistik dan Sastra, 2021)
This study aims to describe the form of gender discrimination in the novel Perempuan Terpasung by Hani Naqshabandi. Data collection was carried out in three stages (1) reading and understanding the novel Perempuan Terpasung by Hani Naqshabandi with the aim of getting an overall understanding of the contents of the novel to be studied, (2) determining the main character and companion figures in the novel Perempuan Terpasung by Hani Naqshabandi for use tracking gender discrimination data, (3) identifying data relating to the form of gender discrimination obtained from data sources, namely the novel Perempuan Terpasung by Hani Naqshabandi. This type of research is qualitative research and uses content analysis techniques. The results showed that the forms of discrimination experienced by female leaders were seen in aspects of marginalization, subordination, stereotyping, and violence. The most dominant form experienced by female leaders in the novel Perempuan Terpasung is discrimination in the form of stereotypes, namely the assumption that the main task of women is to serve their husbands, their duties and functions are only to carry out work related to domestic or domestic work.